Problems of development of the circular economy as a factor in Russia’s sustainable development - N. G. Gadzhiev; N. A. Murzak; A. E. Mitenkova; O. V. Skripkina; S. A. Konovalenko (Юг России: экология, развитие)
Aim. To investigate the process of formation of the circular economy in Russia within the framework of ensuring sustainable development and to identify the problems of forming a circular economy and the barriers that hinder the process of implementing business models of a circular economy in enterprises.Materials and Methods. Our study is based on systems analysis, comparative and statistical methods.Discussion. The research results have confirmed the necessity of transition to the formation a circular economy in Russia. This is despite the fact that the volume of recycled waste arising from production and consumption in Russia is growing faster than that of its generation, the actual proportion of recycling and waste disposal is growing rather slowly (somewhat more than 50%), while the proportion of the volume of production and consumption waste placed at company facilities, on average, amounted to 50% for the period analysed. Greenhouse gas emissions also have a negative impact on the environment with those of the "Economy" sector accounting for almost 79% thus determining the relevance of transition to renewable energy.Conclusion. The transition to a circular economy, in particular as a result of the use of renewable energy, will reduce the negative impact of anthropogenic pressure on the environment and ensure a balance between the environmental, economic and social components of sustainable development.